MODELING OF THE INFORMATION-ANALYTICAL SYSTEM OF ACCOUNTING OF SCIENTIFIC WORKS OF UNIVERSITY EMPLOYEES - Akhmetzhanova, Sh.; Adilova, A. (Scientific Journal of Astana IT University, 2021)
The article describes development of an information system for storing the results of scientific work of the Taraz Regional University named after M. H. Dulaty. Today, such works are organized in a non-automated way. In addition, this leads to a number of anomalies, namely: errors in data entry, their duplication, complexity of preparing reports, difficulties in finding the necessary information because of the complexity of the information system. In order to solve such problems and to improve data quality it is necessary to create a research analytical information system that allow to reduce manual workload and use simple and convenient access system to stored information using various queries. The aspects of creating a research information system described in the article can be implemented in any higher educational institution of the Republic of Kazakhstan. In order to create an information system, a functional model was created using the Fusion Process Modeler 4.0 CASE-system. After the decomposition of the diagram, five functions were identified: “Accounting the research staff”, “Research”, “Accounting the publications”, “Dissertation defense”, “Reporting”. Modern tools are used in the development of a system for analyzing and monitoring the research activities of TarRU: PHP scripting language, which is widely used for web applications, JavaScript, which is well known as a scripting language for interactivity on web pages in browsers, Microsoft SQL Server relational database management system.